Sensory evaluation of meat from entire male pigs raised with different feeding and housing conditions - Pinto, Ricardo (2018)
Introduction: Boar taint is an off-odour/off-flavour found in meat from entire male pigs due to two main compounds: androstenone and skatole. The incidence of boar taint is of concern when considering the use of entire males for pork meat production. Objectives: This study aims at evaluating sensory characteristics of meat from entire male pigs raised under specific conditions in order to reduce or eliminate the boar taint. Methods: Belly meat from entire male pigs raised under six different conditions (normal housing versus improved housing) and feeding with different levels of added inulin (0%, 3% and 6%) was analysed. A Quantitative Descriptive Analysis (QDA®) methodology was applied to samples, previously cooked and presented in closed jars, and the panel, composed by 10 trained panellists, was asked to assess odour and flavour of skatole and androstenone, texture and sweet flavour. Results: Significant differences (p<0.05) were found between samples concerning skatole and androstenone odour and flavour, and texture compared to control samples. Conclusions: As expected, the boar taint was stronger in samples where no addition of inulin and no improved conditions were applied. It can be concluded that the inulin addition into pig feed have positive effects when conjugated with better housing conditions.